A chlorine-resistant composition for spandex and preparation method thereof

By using a double-layer coating technology on spandex fiber, combined with water magnesite with decrystallized water and specific coating agents, the chlorine resistance and spinning solution stability of spandex fibers under chlorine bleaching conditions is solved, and the problem of chlorine resistance and spinning solution stability of spandex fibers is achieved. Efficient suspension stability and fluidity meet the needs of industrial production.

CN118854474BActive Publication Date: 2024-12-31PENGLAI SPARK CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327869.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The physical properties of spandex fibers are reduced under chlorine bleaching conditions, and the existing compositions that improve chlorine resistance have poor dispersion fluidity and suspension stability in spinning solutions, making it difficult to meet industrial production needs.

Method used

Using de-crystallized water as the substrate, the inner layer is coated with titanate and the outer layer is made of cycloalkane acid, polyetheramine, trimethylolalkane, acrylic resin and poly The ether-modified styrene maleic anhydride resin copolymer is composed of which controls the water content of the coating matrix and the thickness of the coating layer, and improves the chlorine resistance and fluidity of the composition.

Benefits of technology

The suspension stability and fluidity in the spandex spinning solvent are significantly improved, ensuring that the composition does not settle within 7 days, and the passing rate reaches more than 95%, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a chlorine-resistant composition for spandex and a preparation method thereof, and belongs to the technical field of spandex spinning. The chlorine-resistant composition for spandex comprises a substrate, which is hydromagnesite with part of crystal water removed; a coating layer, which is uniformly coated on the substrate by a coating agent, and comprises an inner layer and an outer layer, which are coated with different coating agents. The chlorine-resistant composition for spandex prepared by the invention has good dispersion fluidity and suspension stability in a spinning solvent, has no thixotropy, can pass through a 1250-mesh screen after grinding, and has strong chlorine resistance using the composition of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spandex spinning, in particular to a chlorine-resistant composition for spandex and a preparation method thereof. Background Art

[0002] Spandex is a representative polyurethane elastic fiber that can maintain high elasticity and has excellent physical properties such as tensile stress and recovery force. Therefore, it can be widely used in underwear, socks, sports and leisure clothing, etc. However, polyurethane, which is the main component of spandex, will have its physical properties greatly reduced when chlorine bleached. Therefore, if a swimsuit made of spandex and nylon is worn in a swimming pool with an active chlorine content of 0.5 to 3.5 ppm or higher, its strength and other physical properties will be reduced.

[0003] In order to solve the technical problem of deterioration due to chlorine, efforts have been made to improve the resistance of spandex fibers; the traditional method is: the matrix is ​​basic magnesium carbonate, which has an unstable composition and often contains harmful impurity elements such as Cl, S, P, and Fe. Although artificially synthesized ones have fewer impurities, they are expensive and not suitable for industrial production; hydromagnesite is heated at 400°C or above to remove all adsorbed water and crystal water, which is difficult to control (dehydration); the coating materials mainly use stearic acid and its salts and derivatives, silicone substances, SiO2, etc., which have limitations; the coating process is mostly one-time coating or no coating, the coating effect is better than no coating, and the one-time coating effect is unstable.

[0004] In addition, the existing compositions for improving the durability of spandex fibers have problems such as poor dispersion fluidity and suspension stability in the spinning solution.

[0005] Therefore, there is an urgent need to develop a chlorine-resistant composition for spandex and a preparation method, which has low material cost and can effectively improve the technical problems of the spandex fiber-resistant composition in the spinning solution, such as poor dispersion fluidity and suspension stability, while maintaining its strong chlorine resistance. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a chlorine-resistant composition for spandex, comprising a substrate, which is hydromagnesite with some crystal water removed; a coating layer, which is uniformly coated on the substrate by a coating agent, and the coating layer comprises an inner layer and an outer layer, and the inner layer and the outer layer are coated by different coating agents.

[0007] Furthermore, the inner layer is coated with titanate, and the outer layer is coated with one or more of cycloalkane acid, polyetheramine, trihydroxymethylalkane, trihydroxymethylaminoalkane, acrylic resin, polyether-modified styrene maleic anhydride resin copolymer, and polyether-modified styrene acrylic copolymer.

[0008] Another object of the present invention is to provide a method for preparing the above-mentioned chlorine-resistant composition for spandex, comprising the following steps: S1: batching, weighing hydromagnesite containing crystal water; S2: drying, drying the hydromagnesite containing crystal water weighed in S1 to obtain hydromagnesite with partial crystal water removed; S3: aging, aging the hydromagnesite with partial crystal water removed in S2 for at least 24 hours to homogenize the water; S4: inner layer coating, placing the aged material and a certain mass of inner layer coating agent in a modifier for dry coating; S5: crushing, crushing the coated material; S6: outer layer coating, placing the crushed material and a certain mass of inner layer coating agent in a modifier for secondary dry coating, and then cooling naturally to obtain the target product. Further, in S1, the mass ratio of the dolomite to the hydromagnesite is 0.05-0.15:1.

[0009] Furthermore, in S2, the titanate is propyl dioleyloxy (dioctyl phosphate) titanate or isopropyl trioleyloxy titanate or bis(dioctyl pyrophosphate) ethylene titanate.

[0010] Furthermore, the amount of the inner coating agent is 0.5-2% of the mass of the substrate, and the amount of the outer coating agent is 0.5-3% of the mass of the substrate.

[0011] Furthermore, in S2, the drying temperature is 320-380°C.

[0012] Furthermore, in S1, the water content of the hydromagnesite from which some crystal water has been removed is 5% or less of the total mass.

[0013] Furthermore, in S1, the water content of the hydromagnesite from which some crystal water has been removed is 3-5% of the total mass.

[0014] Furthermore, in S4, the inner layer coating temperature is 40-120° C., and the coating time is 10-60 min.

[0015] Furthermore, in S5, after crushing, the particle size D90 of the hydromagnesite from which some crystal water has been removed is ≤10 μm.

[0016] Furthermore, in S6, the outer layer coating temperature is 70-120°C, and the coating time is 10-60 minutes.

[0017] The beneficial effects of the chlorine-resistant composition for spandex and the method for making the same according to the embodiments of the present invention include:

[0018] (1) The chlorine-resistant composition for spandex prepared by the present invention has no thixotropy and good fluidity when used in a spandex spinning solvent; and has good suspension stability in a spandex spinning solvent, and can achieve a technical effect of being stable and non-sedimentary for at least 7 days; the composition is ground and dispersed by a grinder and heated at 3 kg / cm 2Under the pressure of , it can pass through the 1250 mesh filter smoothly, and the passing rate is more than 95% of the added amount.

[0019] (2) The preparation of the chlorine-resistant composition for spandex of the present invention adopts double-layer coating. By controlling the water content of the coating substrate, the thickness of the coating layer of the coating substrate, the selection of the coating agent and the coating process, the prepared chlorine-resistant composition not only has strong chlorine resistance, but also has good suspension stability, fluidity and permeability in the spandex spinning solvent.

[0020] (3) The preparation method of the chlorine-resistant composition for spandex of the present invention is simple and low in cost. The inner layer coating agent is evenly coated on the active sites on the substrate. After crushing, the outer layer coating agent is partially coated on the inner layer coating agent and partially coated on the active sites on the newly generated surface of the substrate. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] On one hand, the present invention provides a chlorine-resistant composition for spandex, comprising a substrate, which is hydromagnesite with some crystal water removed; a coating layer, which is uniformly coated on the substrate by a coating agent, and comprises an inner layer and an outer layer, and the inner layer and the outer layer are coated by different coating agents.

[0023] The chlorine-resistant composition for spandex prepared by the present invention has no thixotropy and good fluidity when used in a spandex spinning solvent; and has good suspension stability in a spandex spinning solvent, and can achieve a technical effect of being stable and non-sedimentary for at least 7 days; the composition ground and dispersed by a grinder is subjected to a pressure of 3 kg / cm 2 Under the pressure of , it can pass through the 1250 mesh filter smoothly, and the passing rate is more than 95% of the added amount.

[0024] The preparation of the chlorine-resistant composition for spandex of the present invention adopts double-layer coating. By controlling the water content of the coating substrate, the thickness of the coating layer of the coating substrate, the selection of the coating agent and the coating process, the prepared chlorine-resistant composition not only has strong chlorine resistance, but also has good suspension stability, fluidity and permeability in the spandex spinning solvent.

[0025] Specifically, the inner layer is coated with titanate, and the outer layer is coated with one or more of cycloalkane acid, polyetheramine, trimethylolalkane, trimethylolaminoalkane, acrylic resin, polyether-modified styrene maleic anhydride resin copolymer, and polyether-modified styrene acrylic copolymer.

[0026] When titanate is selected as the inner coating agent and one or more of cyclohexane acid, polyetheramine, trihydroxymethylalkane, trihydroxymethylaminoalkane and acrylic resin is selected as the outer coating agent, the obtained chlorine-resistant composition product for spandex has good suspension stability, fluidity and permeability.

[0027] It should be noted that the titanate in the present invention includes but is not limited to propyl dioleyl (dioctyl phosphate) titanate (CAS: 61417-49-0), isopropyl trioleyl titanate (CAS: 136144-62-2), bis (dioctyl pyrophosphate) ethylene titanate (CAS: 65467-75-6); cycloalkane acid refers to a saturated carboxylic acid containing one or more five-membered rings or six-membered rings of C6-C30; polyetheramine is obtained by ammoniation of polyethylene glycol, polypropylene glycol or ethylene glycol / propylene glycol copolymer under high temperature and high pressure, and has a molecular weight of 300-3000; trimethylolalkane includes Including but not limited to trimethylolpropane and trimethylolheptane; trimethylolaminoalkane includes but is not limited to trimethylolaminomethane (CAS: 77-86-1); acrylic resin (CAS: 9003-01-4) is obtained by copolymerizing (meth)acrylate and styrene with other acrylic esters; polyether-modified styrene maleic anhydride resin copolymer and polyether-modified styrene acrylic copolymer specifically refer to styrene maleic anhydride resin copolymer and styrene acrylic copolymer polymers obtained by polymerization of monomers modified with polyether substances, but are not limited to this method and can also be obtained by other methods.

[0028] Another aspect of the present invention provides a method for preparing the above-mentioned chlorine-resistant composition for spandex, comprising the following steps: S1: batching, weighing hydromagnesite containing crystal water; S2: drying, drying the hydromagnesite containing crystal water weighed in S1 to obtain hydromagnesite with some crystal water removed; S3: aging, aging the hydromagnesite with some crystal water removed in S2 for at least 24 hours to homogenize the moisture; S4: inner layer coating, placing the aged material and a certain mass of inner layer coating agent into a modifier for dry coating; S5: crushing, crushing the coated material; S6: outer layer coating, placing the crushed material and a certain mass of inner layer coating agent into a modifier for secondary dry coating, and then naturally cooling to obtain the target product.

[0029] The preparation method of the chlorine-resistant composition for spandex of the present invention is simple and has low cost. The inner coating agent is evenly coated on the active sites on the substrate. After crushing, the outer coating agent is partially coated on the inner coating agent and partially coated on the active sites on the newly generated surface of the substrate.

[0030] Specifically, in S2, the titanate includes propyl dioleyl (dioctyl phosphate) titanate, isopropyl trioleyl titanate, and bis (dioctyl pyrophosphate) ethylene titanate.

[0031] When the above titanate is selected, the chlorine resistance, suspension fluidity and grinding pass rate of the product can be guaranteed to be high.

[0032] Specifically, the amount of the inner coating agent is 0.5-2% of the mass of the substrate, and the amount of the outer coating agent is 0.5-3% of the mass of the substrate.

[0033] By limiting the amount of inner and outer coating agents, it is ensured that the thickness of the inner and outer coating films will not be too thick to affect the chlorine resistance, nor too thin to affect the suspension stability of the composition in the spinning solution.

[0034] Preferably, the amount of the outer coating agent is 1.1-2 times the amount of the inner coating agent.

[0035] When the amount of the outer coating agent is 1.1-2 times that of the inner coating agent, the suspension stability of the composition in the spinning solution is the best.

[0036] Specifically, in S2, the drying temperature is 320-380°C.

[0037] If the drying temperature is too high, the crystal structure of hydromagnesite will be destroyed, thus affecting its chlorine resistance; if the drying temperature is too low, the crystal water cannot be separated more quickly.

[0038] Specifically, in S1, the water content of the hydromagnesite from which some crystal water has been removed is 3-5% of the total mass.

[0039] If dehydration is not done, the impact will be reflected in the subsequent spandex production process; if the drying temperature is too high, the hydromagnesite will partially decompose and generate oxides during the dehydration process, and the hardness will increase, which will have an adverse effect on the spandex production process, causing the grinding time to be extended or even the grinding to be not fine enough, resulting in filter clogging.

[0040] Specifically, in S4, the inner layer coating temperature is 40-120° C., and the coating time is 10-60 min.

[0041] Specifically, in S5, after the crushing, the particle size D90 of the hydromagnesite from which some crystal water is removed is ≤10 μm.

[0042] It should be noted that D90 refers to the particle size value corresponding to when the cumulative distribution percentage from small to large reaches 90% in the particle size distribution.

[0043] Specifically, in S6, the outer layer coating temperature is 70-120°C, and the coating time is 10-60 minutes.

[0044] The hydromagnesite used in the embodiment of the present invention contains 15% of the total mass of crystal water before drying.

[0045] The method for determining the crystal water content in the present invention is conventional thermogravimetric method, which is measured using a TG-DTG instrument.

[0046] It should be noted that the grinding conditions in the embodiments of the present invention specifically refer to: the coated sample and DMAC are mixed into a slurry at a solid content of 20%, and the slurry is added to a sand mill and ground for 3 hours; the test results of no thixotropy and good fluidity specifically refer to: the slurry flows freely without re-thickening; large thixotropy and poor fluidity specifically refer to: when the slurry is sheared, the consistency decreases and the fluidity is restored, and when the shearing is stopped, the consistency increases and the fluidity is lost or partially lost; after grinding, it can pass through means: the composition ground and dispersed by the grinder is placed at 3kg / cm 2 It can pass through a 1250 mesh filter under a pressure of 3kg / cm 2 Under the pressure of 1250 mesh filter, it cannot pass smoothly, the passing rate is less than 10% of the added amount, and even clogs the filter.

[0047] Example 1

[0048] S1: Ingredients: weigh 100 g of hydromagnesite containing crystal water;

[0049] S2: Drying: Drying the hydromagnesite containing crystal water weighed in S1, wherein the drying temperature is 320°C, the drying time is 2h, and the weight after drying is 87.7g, and the water content accounts for 3% of the total hydromagnesite mass;

[0050] S3: aging, the hydromagnesite with some crystal water removed in S2 is mixed evenly and aged for 48 hours to homogenize the water content;

[0051] S4: inner layer coating, the aged material and 1g of coating agent propyl dioleic acid acyloxy (dioctyl phosphate acyloxy) titanate are placed in a modifier for dry coating, the coating temperature is 80°C, and the coating time is 35min;

[0052] S5: crushing, crushing the coated material, the particle size of the crushed material D90≤10μm;

[0053] S6: outer layer coating, the crushed material and 1.6g of coating agent acrylic resin are placed in a modifier for secondary dry coating, wherein the coating temperature is 70°C and the coating time is 60min. After natural cooling, the chlorine-resistant composition I1 for spandex is obtained.

[0054] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0055] Example 2

[0056] S1: Ingredients: weigh 100 g of hydromagnesite containing crystal water;

[0057] S2: Drying: Drying the hydromagnesite containing crystal water weighed in S1, wherein the drying temperature is 380°C, the drying time is 1.5h, and after drying, the weight of the mixture is 89.5g, and the water content accounts for 5% of the total hydromagnesite mass;

[0058] S3: aging, the hydromagnesite with some crystal water removed in S2 is mixed evenly and aged for 24 hours to homogenize the water content;

[0059] S4: inner layer coating, put the aged material and 1.2g of coating agent isopropyl trioleate acyloxy titanate into the modifying machine for dry coating, the coating temperature is 120℃, and the coating time is 10min;

[0060] S5: crushing, crushing the coated material, the particle size of the crushed material D90≤10μm;

[0061] S6: outer layer coating, the crushed material and 2.4g of coating agent polyetheramine are placed in a modifier for secondary dry coating, wherein the coating temperature is 120°C, the coating time is 10min, and after natural cooling, the chlorine-resistant composition I2 for spandex is obtained.

[0062] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0063] Example 3

[0064] S1: Ingredients: weigh 100g hydromagnesite;

[0065] S2: Drying: Drying the hydromagnesite containing crystal water weighed in S1, wherein the drying temperature is 350°C and the drying time is 2 hours. After drying, the weight of the mixture is 88.5 g, and the water content accounts for 4% of the total hydromagnesite mass;

[0066] S3: aging, the hydromagnesite with some crystal water removed in S2 is mixed evenly and aged for 48 hours to homogenize the water content;

[0067] S4: inner layer coating, the aged material and 2.1g of coating agent bis(dioctyloxypyrophosphate)ethylene titanate are placed in a modifying machine for dry coating, the coating temperature is 80°C, and the coating time is 35min;

[0068] S5: crushing, crushing the coated material, the particle size of the crushed material D90≤10μm;

[0069] S6: outer layer coating, the crushed material and 3.2g of coating agent cyclohexane acid are placed in a modifier for secondary dry coating, wherein the coating temperature is 100°C and the coating time is 35min. After natural cooling, the chlorine-resistant composition I3 for spandex is obtained.

[0070] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0071] Example 4

[0072] S1: Ingredients: weigh 100g hydromagnesite;

[0073] S2: Drying: Drying the hydromagnesite containing crystal water weighed in S1, wherein the drying temperature is 350°C and the drying time is 2 hours. After drying, the weight of the mixture is 88.5 g, and the water content accounts for 4% of the total hydromagnesite mass;

[0074] S3: aging, the hydromagnesite with some crystal water removed in S2 is mixed evenly and aged for 48 hours to homogenize the water content;

[0075] S4: inner layer coating, put the aged material and 0.5g coating agent isopropyl trioleate acyloxy titanate into the modifying machine for dry coating, the coating temperature is 90℃, and the coating time is 30min;

[0076] S5: crushing, crushing the coated material, the particle size of the crushed material D90≤10μm;

[0077] S6: outer layer coating, put the crushed materials 1.5g coating agent acrylic resin and 1.5g coating agent polyetheramine into a modifying machine for secondary dry coating, wherein the coating temperature is 90°C, the coating time is 30min, and after natural cooling, the chlorine-resistant composition I4 for spandex is obtained.

[0078] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0079] Example 5

[0080] Compared with Example 3, the amount of bis(dioctyloxypyrophosphate)ethylene titanate used as the outer coating agent is 0.5 g, and the other aspects are the same as in Example 3, thereby obtaining a chlorine-resistant composition I5 for spandex.

[0081] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0082] Example 6

[0083] Compared with Example 3, the amount of bis(dioctyloxypyrophosphate)ethylene titanate used as the outer coating agent is 2.3 g, and the other parts are the same as Example 3, thereby obtaining a chlorine-resistant composition I6 for spandex.

[0084] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0085] Comparative Example 1 (Compared with Example 1, inner coating agent was used in both coatings)

[0086] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 1, except that the same coating agent, propyl dioleyl (dioctyl phosphate) titanate, was used for both coatings.

[0087] The chlorine-resistant composition for spandex finally obtained is D1.

[0088] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0089] Comparative Example 2 (Compared with the example, both coatings used an outer coating agent)

[0090] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 1, except that the same coating agent, acrylic resin, was used in both coatings.

[0091] The chlorine-resistant composition for spandex finally obtained is D2.

[0092] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0093] Comparative Example 3 (Drying and dehydration temperature is too high)

[0094] The chlorine-resistant composition for spandex was prepared by the same method as in Example 1, except that the drying and dehydration temperature of the matrix hydromagnesite was 430°C.

[0095] The chlorine-resistant composition for spandex finally obtained is D3.

[0096] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0097] Comparative Example 4 (Too much inner coating agent)

[0098] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 2, except that the amount of the inner layer coating agent, isopropyl trioleyl titanate, was 6 g.

[0099] The chlorine-resistant composition for spandex finally obtained is D4.

[0100] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0101] Comparative Example 5 (too little inner coating agent)

[0102] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 2, except that the amount of the inner layer coating agent, isopropyl trioleyl titanate, was 0.01 g.

[0103] The chlorine-resistant composition for spandex finally obtained is D5.

[0104] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0105] Comparative Example 6 (Excessive coating agent on the outer layer)

[0106] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 1, except that the amount of acrylic resin used as the outer coating agent was 7 g.

[0107] The chlorine-resistant composition for spandex finally obtained is D6.

[0108] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0109] Comparative Example 7 (Too little outer coating agent)

[0110] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 1, except that the amount of acrylic resin used as the outer coating agent was 0.01 g.

[0111] The chlorine-resistant composition for spandex finally prepared is D7.

[0112] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0113] Comparative Example 8 (Inner layer coating agent is polyetheramine)

[0114] The chlorine-resistant composition for spandex was prepared in the same manner as in Example 1, except that the inner coating agent was polyetheramine.

[0115] The chlorine-resistant composition for spandex finally prepared is D8.

[0116] The performance indicators of the finally prepared chlorine-resistant composition for spandex are shown in Table 1.

[0117] Table 1. Performance indexes of chlorine-resistant compositions for spandex prepared in Examples 1 to 7 and Comparative Examples 1 to 8

[0118]

[0119] It can be seen from the experimental data of Examples 1 to 6 that the chlorine-resistant composition for spandex prepared by the preparation method of the present invention has good dispersion fluidity, is beneficial to maintaining its physical properties, is easy to maintain its better suspension stability during the spandex production process, and is not prone to secondary agglomeration and sedimentation to block the screen. It was found through experiments that when the inner layer coating agent is composed of titanate and other outer layer coating agents, the ground slurry can naturally pass through the screen without pressurization, and its passability is better.

[0120] It can be seen from the experimental data of Example 1 and Comparative Examples 1 and 2 that when the coating agent is the same for both applications, both inner coating agents or both outer coating agents are used, the coating effect is equivalent to that of using only one substance, which is characterized by large thixotropy, poor fluidity, easy sedimentation, etc., and some even clog the filter screen after grinding.

[0121] It can be seen from Example 1 and Comparative Example 3 that when the drying temperature exceeds the temperature of the present invention, the hydromagnesite partially decomposes to generate oxides, and the hardness becomes higher, which not only has an adverse effect on the spandex production process, but also causes the grinding time to be prolonged or even the grinding is not fine enough, resulting in clogging of the filter.

[0122] It can be seen from the experimental data of Example 2 and Comparative Examples 4 and 5 that when the amount of inner layer coating agent used is too much or too little, the existence of the outer layer or the inner layer is weakened, which is equivalent to the effect of a single coating. Its fluidity decreases, its thixotropy increases, it is easy to settle, etc., and some even clog the filter screen after grinding.

[0123] It can be seen from the experimental data of Example 1 and Comparative Examples 6 and 7 that when the amount of outer coating agent used is too much or too little, the existence of the inner layer or the outer layer is weakened, which is equivalent to the effect of a single coating. Its fluidity decreases, its thixotropy increases, it is easy to settle, etc., and some even clog the filter screen after grinding.

[0124] It can be seen from the experimental data of Example 1 and Comparative Example 8 that when the inner coating agent portion is polyetheramine, the thixotropy is large and the fluidity is poor.

[0125] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A chlorine-resistant composition for spandex, characterized in that: Used in spandex spinning solvent, comprising a substrate, the substrate is hydromagnesite with part of crystal water removed; a coating layer, the coating layer is evenly coated on the substrate by a coating agent, the coating layer comprises an inner layer and an outer layer, the inner layer and the outer layer are coated by different coating agents; The inner layer is coated with titanate, and the outer layer is coated with one or more of cycloalkane acid, polyetheramine, trimethylolalkane, trimethylolaminoalkane, acrylic resin, polyether-modified styrene maleic anhydride resin copolymer, and polyether-modified styrene acrylic copolymer; The titanate is propyl dioleyl (dioctyl phosphate) titanate or isopropyl trioleyl titanate or bis (dioctyl pyrophosphate) ethylene titanate; The amount of the inner coating agent is 0.5-2% of the mass of the substrate, and the amount of the outer coating agent is 0.5-3% of the mass of the substrate; The water content of the partially dehydrated hydromagnesite is 3-5% of the total mass.

2. A method for preparing the chlorine-resistant composition for spandex according to claim 1, characterized in that: The following steps are involved: S1: Ingredients: weigh hydromagnesite containing crystal water; S2: Drying: drying the hydromagnesite containing crystal water weighed in S1 to obtain hydromagnesite with partially crystal water removed; S3: aging, aging the partially dehydrated hydromagnesite in S2 for at least 24 hours to homogenize the water content; S4: inner coating, put the aged material and inner coating agent into the modifying machine for dry coating; S5: crushing, crushing the coated material; S6: outer layer coating, the crushed material and the inner layer coating agent are placed in a modifier for secondary dry coating, and then naturally cooled to obtain the target product.

3. The method for preparing the chlorine-resistant composition for spandex according to claim 2, characterized in that: In S2, the drying temperature is 320-380°C.

4. The method for preparing the chlorine-resistant composition for spandex according to claim 2, characterized in that: In S4, the inner layer coating temperature is 40-120°C and the coating time is 10-60 minutes.

5. The method for preparing the chlorine-resistant composition for spandex according to claim 2, characterized in that: In S5, after the pulverization, the particle size D90 of the hydromagnesite from which some crystal water is removed is ≤10 μm.

6. The method for preparing the chlorine-resistant composition for spandex according to claim 2, characterized in that: In S6, the outer layer coating temperature is 70-120°C and the coating time is 10-60 minutes.